Three-dimensional nanodosimetric characterisation of proton track structure. (November 2020) - Braunroth, Thomas; Nettelbeck, Heidi; Ngcezu, Sonwabile A.; Rabus, Hans
Abstract: This work presents a detailed investigation into the nanodosimetric properties of the track structure of protons in water at energies relevant for proton radiotherapy. The ionization component of the tracks had been simulated in previous work using Geant4-DNA for proton start energies between 1 MeV and 100 MeV. From the simulation results, the frequency distribution of ionization clusters formed in nanometric target volumes was obtained in dependence of the impact parameter of the proton trajectory with respect to the target center. In the track core, targets of cylindrical shape and a size comparable to a short segment of DNA were used for scoring ionization cluster size distributions. For the penumbra region, three different options for defining the cylinder shell sectors were investigated, with each cylinder shell sector volume the same as the cylinder target volume. The radial distributions were numerically integrated to obtain the effective track cross sections with respect to different nanodosimetric parameters. Graphically displaying the radial dependence in a similar way as microdosimetric distributions allowed elucidating the contribution of different radial distances to the overall radial integral of the quantities under consideration. Furthermore, it was tested how well the radial dependence of the nanodosimetric parameters could be fitted with a model function derived in literature for the radial energy deposition in proton tracks. It was found that this model function allows describing only the radial dependence of the total frequency of nanometric targets where ionizations occur. The deviation from a 1/ r 2 -dependence of the radial dependence of the frequency of targets receiving more than a minimum number of ionizations (exceeding one) includes a second peak centred around 10 nm radial distance from the proton trajectory. Highlights: Proton track segments in water simulated with Geant4-DNA for start energies between 1 MeV and 99 MeV were analyzed. Radial dependence of ionization cluster frequencies was determined for all occurring distances from the proton trajectory. Different scoring options for the penumbra region were investigated. Mixed linear and semi-logarithmic plot presentation of the results elucidates the contributions of different radial ranges. Complementary cumulative ionization cluster frequencies at minimum number two or higher show an additional "peak".